Analisis Unsur Etnomatematika pada Struktur Bangunan Rumah Adat Tongkonan di Tana Toraja - Nur Wahidin Ashari; Nurwahidah Nurwahidah; Andi Nurazizah; Arfianty Amin; Nur Anisa Syam (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
The Tongkonan traditional house of Tana Toraja represents a form of indigenous architecture with strong social and cultural functions. However, the mathematical elements embedded in its structural design have not been widely utilized in contextual mathematics learning. This study aims to explore the mathematical concepts found in the physical structure of the Tongkonan and to examine opportunities for integrating these concepts into culture-based mathematics instruction. Employing a descriptive qualitative approach, data were collected through observations and interviews, and analyzed using domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The findings reveal that the architectural form of the Tongkonan embodies concepts of symmetry, roof-slope proportions, construction patterns, relationships among measurements, and principles of similarity, particularly as reflected in the Rambu Solo’ ceremonial context. These results highlight geometric regularities relevant to the development of ethnomathematics. Overall, the study contributes to the development of more applicable ethnomathematics-based mathematics learning models in schools.